p Pengaruh model pembelajaran Terintegrasi Problem Based Learning dan Numbered Head Together Terhadap Hasil Belajar dan Berpikir Kritis Ssiswa Kelas X SMA Negeri 16 Samarinda: Pengaruh model pembelajaran Terintegrasi Problem Based Learning dan Numbered Head Together Terhadap Hasil Belajar dan Berpikir Kritis Ssiswa Kelas X SMA Negeri 16 Samarinda - Indriani, Yeni; Kurniawati, Zenia Lutfi; Masitah; Lumowa, Sonja V.T (UNIB Press, 2024)
This classroom action research aimed to determine the learning outcomes and level of critical thinking demonstrated by the students in the class. The researchers utilized a quasi-experimental study methodology, especially employing a research design called the one group pretest-posttest design. The methodology used was the Independent Sample t-Test to analyze learning outcomes, with a significance level of 5%. This research results a substantial significance. The two-tailed test result is statistically significant because the p-value (0.000) is smaller than the significance level (0.05), or the t-statistic (3.268) is larger than the crucial t-value (2.01063). This study suggests that the combined use of integrated problem-based learning (PBL) and numbered head together (NHT) learning models significantly affect the learning outcomes of class X students at SMA Negeri 16 Samarinda.